Libraries in Fourth Five Year Plan - Planning Commission (Planning Commission, Government of India, 1997)
The report on library development during India’s Fourth Five Year Plan highlights the critical role of public libraries in promoting literacy and supporting educational objectives amid widespread illiteracy. In 1964, a large majority of the population remained illiterate, despite constitutional guarantees of free elementary education. Public library services were inadequately funded, receiving only a fraction of the educational budget, with per capita expenditure far below that of primary education. The report advocates for a phased increase in financial support, structural reforms to establish a multi-tiered library system with district libraries as hubs, and comprehensive training programs to enhance the capacity of librarians. By integrating libraries as essential components of the educational system, the report argues that India can significantly improve literacy rates, strengthen educational outcomes, and advance broader societal goals of equality and social justice.
A Paper Prepared for the Planning Commission's Working Group on Libraries By N. C. Chakravarty
A Paper Prepared for the Planning Commission's Working Group on Libraries By N. C. Chakravarty
Keywords: Library Development; Public Libraries; Literacy Promotion; Elementary Education; Educational Planning; Fourth Five Year Plan; Budget Allocation; District Libraries; Staff Training; Library System Restructuring; Social Awareness; Educational Resources